Chitosan - alginate multilayered films with gradients of physical cues - Silva, J. (2014)
In general cell types are sensitive to mechanical stimulus of the surrounding environment which affects several cell properties. Thus, the development of biocompatible coatings with tuned mechanical properties are a current challenge, since gradients of physical signals are often applied in cellular processes to reconstruct the complex anisotropic environment presented by extracellular matrix (ECM) (1,2). Layer-by-layer (LbL) appears as a powerful tool since it allows the development of biomimetic multilayer films with well–controlled structures at both the nano and micro-scales (2). This study aimed to develop chitosan (CHIT) and alginate (ALG) polyelectrolyte multilayers with gradients of physical cues generated by changing the reaction time of genipin crosslinking as a function of controlled distance.